Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.5535/arm.2018.42.3.483
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Pure Ulnar Sensory Neuropathy Around the Hypothenar Area Using Orthodromic Inching Sensory Nerve Conduction Study: A Case Report

Abstract: Ulnar neuropathy at the wrist is an uncommon disease and pure ulnar sensory neuropathy at the wrist is even rarer. It is difficult to diagnose pure ulnar sensory neuropathy at the wrist by conventional methods. We report a case of pure ulnar sensory neuropathy at the hypothenar area. The lesion was localized between 3 cm and 5 cm distal to pisiform using orthodromic inching test of ulnar sensory nerve to stimulate at three points around the hypothenar area. Ultrasonographic examination confirmed compression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…Combined EMG and ultrasound have been shown to help localize the injury to the level of the brachial plexus cords, branches, or peripheral nerve. 11 , 12 , 13 , 14 In case 1, MRI of the brachial plexus showed abnormalities at the level of the infraclavicular brachial plexus. However, because MRI of the brachial plexus is not routinely obtained after vascular procedures, it is unclear if findings represent scar or expected postoperative changes vs pathological compression.…”
Section: Discussionmentioning
confidence: 95%
“…Combined EMG and ultrasound have been shown to help localize the injury to the level of the brachial plexus cords, branches, or peripheral nerve. 11 , 12 , 13 , 14 In case 1, MRI of the brachial plexus showed abnormalities at the level of the infraclavicular brachial plexus. However, because MRI of the brachial plexus is not routinely obtained after vascular procedures, it is unclear if findings represent scar or expected postoperative changes vs pathological compression.…”
Section: Discussionmentioning
confidence: 95%
“…Third, cases involving only superficial sensory fibers were not observed in this study, while they have been reported previously. 18 In order to demonstrate patterns involving motor or sensory fibers depending on location and etiology, further studies that include more patients with UNW are required. Fourth, the supramaximal stimulation intensities differed among individuals due to variations in the distance from the surface to the nerve.…”
Section: Discussionmentioning
confidence: 99%